2019
DOI: 10.1111/vru.12756
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic and histopathological features in 8 cats with fibrotic small intestinal stricture

Abstract: Benign stricture is an uncommon cause of chronic small intestinal obstruction in the cat. The purpose of this retrospective case series was to describe the ultrasonographic features, histopathological findings, and clinical presentation in a group of cats with benign small intestinal stricture. Inclusion criteria were cats presenting during the period 2010‐2017, and that had ultrasonography and small intestinal stricture confirmed at surgery. For each cat, clinical data and ultrasonographic findings were retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…Ultrasonographically, strictures were characterised by a segment of bowel with a non-distensible lumen and were identified in the duodenum (1/8), mid- to distal jejunum (4/8) and proximal ileum (3/8). 70 In all cats, there was evidence of moderate to marked gastric and either generalised or segmental small intestinal distension oral to the stenosis indicative of mechanical bowel obstruction. The length of the stenosed segment varied from 2–50 mm.…”
Section: Fibrotic Small Intestinal Stricturementioning
confidence: 94%
See 2 more Smart Citations
“…Ultrasonographically, strictures were characterised by a segment of bowel with a non-distensible lumen and were identified in the duodenum (1/8), mid- to distal jejunum (4/8) and proximal ileum (3/8). 70 In all cats, there was evidence of moderate to marked gastric and either generalised or segmental small intestinal distension oral to the stenosis indicative of mechanical bowel obstruction. The length of the stenosed segment varied from 2–50 mm.…”
Section: Fibrotic Small Intestinal Stricturementioning
confidence: 94%
“…Histopathology revealed transmural pathology, which was characterised by inflammation and marked fibrosis that affected the mucosal layer most severely. 70 Sections from three of the cats enabled the authors to demonstrate that fibrosis was indeed the main contributor to the narrowing of the intestinal lumen. Although the aetiology of the fibrosis in these cats is unknown, infectious agents and/or bowel ischaemia were suggested as potential underlying causes.…”
Section: Fibrotic Small Intestinal Stricturementioning
confidence: 99%
See 1 more Smart Citation
“…29,30 In this study, thrombosis of the cranial mesenteric artery was observed during ultrasound in one dog. The CT features of arterial mesenteric thrombosis have been described in dogs with mucosal necrosis, 31 and ulcerative lesions associated with mesenteric thrombosis and intestinal ischaemia have been documented in cats using grey scale 32 and contrast-enhanced ultrasound. 33 However, in this patient, it is unlikely that thrombosis of the cranial mesenteric artery alone would be sufficient to cause duodenal ischaemia, as the duodenum receives mostly dual arterial supply from the cranial pancreaticoduodenal artery, a branch of the celiac artery and the caudal pancreaticoduodenal artery, a branch of the caudal mesenteric artery.…”
Section: Discussionmentioning
confidence: 99%